2012
DOI: 10.1007/s00167-012-1972-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Low-intensity Pulsed Ultrasound on tendon-bone healing in a transosseous-equivalent sheep rotator cuff model

Abstract: The results of this study indicate that Low-intensity Pulsed Ultrasound may aid in the initial phase of tendon-bone healing process in patients who have undergone rotator cuff repair. This treatment may also be beneficial following other types of reconstructive surgeries involving the tendon-bone interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 52 publications
(72 reference statements)
0
29
1
Order By: Relevance
“…VEGF also plays an important role in normal and abnormal neovascularization [11,12]. Prior studies have shown that LIPUS stimulates the production of VEGF in vitro and in vivo [21,27]. However, in our study there was no major difference in VEGF levels between the two groups.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…VEGF also plays an important role in normal and abnormal neovascularization [11,12]. Prior studies have shown that LIPUS stimulates the production of VEGF in vitro and in vivo [21,27]. However, in our study there was no major difference in VEGF levels between the two groups.…”
Section: Discussioncontrasting
confidence: 80%
“…VEGF protein expression also was not different (p = 0.0124, Fig. 6) between the LIPUS group (23 ± 6; 95% CI, [19][20][21][22][23][24][25][26][27] and the control group (22 ± 6; 95% CI, 18-26).…”
Section: Bmp-2 and Vegf Expressionmentioning
confidence: 90%
“…In order to enhance native tissue healing and improve surgical outcomes, various non-invasive therapeutics have been utilized post-operatively, including ultrasound and shock wave therapy. 16,21 Advantages of non-invasive therapeutic devices include their ease of use, relatively low cost, and ability to be brought into the patient’s home instead of requiring frequent visits to the clinic. Additionally, their use as a post-operative adjuvant therapy does not interfere with surgical techniques or standard rehabilitation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…These non-parametric tests were adopted since our data did not present a normal distribution. The specimen number used in this study is similar to or more than other biomechanical studies investigating repair techniques [25, 30, 31]. The significance level was set to P < 0.05.…”
Section: Methodsmentioning
confidence: 99%